Development Of Islamic Religious Education (IRE) Textbooks Based On Ethnopedagogy Through Local Wisdom In Thematic Learning - Fauzan, Fauzan; Murtadha, Murtadha; Azizah, Azizah (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2024)
This study aims to develop an Islamic Religious Education (IRE) textbook based on ethnopedagogy, which integrates local wisdom into thematic learning, and assess its quality and feasibility. Based on the researcher’s observations in several elementary schools in North Aceh, it was found that, in practice, the concepts were not connected to local culture, which is a critical component of the ethnopedagogical approach. Therefore, the solution proposed by the researcher is to provide teachers with an understanding of the ethnopedagogical approach. The research method used is Research and Development (R&D) with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The study involved 27 elementary school teachers in North Aceh as the sample. The survey results showed that the thematic textbook based on Ethno pedagogy was deemed feasible and practical. Most teachers gave ratings with an average of over 80% on almost all tested indicators. In conclusion, developing the IRE textbook based on ethno-pedagogy successfully integrated local cultural values into IRE learning and positively impacted students’ understanding and attitudes. Implications: This textbook plays a role in preserving and introducing local wisdom to students, indirectly strengthening their cultural identity. By studying local wisdom, students will better appreciate their environment’s cultural heritage and values while integrating religious teachings into their socio-cultural lives. Additional Materials: A teacher training program on implementing local wisdom or initiatives from local governments to develop educational resources based on local culture.